Clinical epidemiology the essentials - Fletcher, Grant S. (Wolters Kluwer, 2021)
"This book is for clinicians-physicians, nurses, physicians' assistants, psychologists, veterinarians, and others who care for patients-who want to understand for themselves the strength of the information base for their clinical decisions"-- Provided by publisher.